Secrecy performance evaluation of cooperative vehicular relay networks against location‐uncertain eavesdroppers. Issue 13 (7th May 2022) - Huang, Shanchuan; Huang, Xiujie; Zhao, Shancheng; Tang, Siyun; Lin, Lei
Abstract: This letter is concerned with the physical layer security of the cooperative vehicular relay network where a source vehicle communicates with a destination vehicle via both a direct link in the presence of a location‐uncertain eavesdropping vehicle and an indirect link with the help of an amplify‐and‐forward relay vehicle. Based on the double‐Rayleigh fading model for all links, an approximate analytical expression of the average secrecy capacity of the considered system is derived. This analysis on the average secrecy capacity is shown to be validated by Monte‐Carlo simulations and numerical computations. The simulation and numerical results also demonstrate the effects of the uncertainty of the eavesdropper's location and the relay's location on the average secrecy capacity.